Detailed analysis of grid connected and islanded operation modes based on P/U and Q/f droop characteristics - Qusay Salem; Khaled Alzaaree (Institute of Advanced Engineering and Science, 2021)
This paper presents a thorough control structure of the distributed generators inside the microgrid during both grid-connected and islanded operation modes. These control structures of the DGs voltage source inverters are implemented in synchronous reference frame (SRF) and controlled using linear PI controllers. By implementing the control structures, the desired real and reactive power can be efficiently transferred to the local loads and the utility load by the microgrid generating units. A modified droop control technique is introduced to facilitate the microgrid performance during both modes of operation. The active and reactive power sharing of the load demand between the utility grid and the microgrid can be performed by this drop control technique during the islanded mode. The system performance during intentional islanding event and utility load increase is investigated. The effectiveness of the offered control structures is confirmed through simulation results during both modes of operation.